Environmental Factors influencing Financial Reporting Practices and Development in Sudan - Abbas, Nawal H (Gezira Journal of Economic and Social Sciences, 2012)
The purpose of this paper is to investigate the factors that shaped and determined the current status of financial reporting practices in Sudan. The methodology adopted is descriptive as well as explanatory. The paper seeks to explore why the financial reporting system in Sudan remained deficient and unsound over an extended period of time. The research relies mainly on Secondary data; both quantitative and qualitative data are used. The analysis involves reviewing areas of the Sudan’s economy, Politics, culture and financial and legal systems for the last two decades; the 1990’s and the 2000’s. The analysis is made in the light of the several environmental factors cited in the literature as being influential in determining the level of development of a country’s financial reporting system. The research has demonstrated that the current status of financial reporting practices in Sudanic substantially influenced and determined by three environments; the external environment of the accounting profession which includes the investment climate, the financial sector characteristics and the cultural factors; the internal environment of the accounting profession which comprises education and training and organizations regulating the profession and the regulatory environment that encompasses regulatory requirements and  degree of enforcement of rules and regulations. This is the first empirical study to investigate the different environments of financial reporting in Sudan and assess their impact on the quality of reported financial information. Thus it may be of help to those concerned with the accounting profession and its development.